2017
DOI: 10.1021/jacs.7b03981
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Transcription: Exponential Synthesis of RNA and Modified RNA

Abstract: There is increasing demand for RNA and modified RNA oligonucleotides, but in contrast to DNA oligonucleotides, they are typically prohibitively expensive to chemically synthesize, and unlike longer RNAs, they are only inefficiently produced by in vitro transcription, especially when modified. To address these challenges, we previously reported the evolution of a thermostable DNA polymerase, SFM4-3, that more efficiently accepts substrates with 2'-substituents. We now show that SFM4-3 efficiently transcribes RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…[26] As an initial exploration of the utility of SFM4-3, we demonstrated that when combined with thermocycling, it can exponentially produce large quantities of RNA or 2'-F RNAv ia ap rocess we refer to as polymerase chain transcription (PCT). [27] In addition, we used SFM4-3 to select 2'-F-modified aptamers and found that the modifications impart increased specificity. [28] While the modified nucleotides accessed by SFM4-3 impart the oligonucleotide products with interesting attributes,both the 2'-F and 2'-OMe moieties leave much functional potential to be desired.…”
mentioning
confidence: 99%
“…[26] As an initial exploration of the utility of SFM4-3, we demonstrated that when combined with thermocycling, it can exponentially produce large quantities of RNA or 2'-F RNAv ia ap rocess we refer to as polymerase chain transcription (PCT). [27] In addition, we used SFM4-3 to select 2'-F-modified aptamers and found that the modifications impart increased specificity. [28] While the modified nucleotides accessed by SFM4-3 impart the oligonucleotide products with interesting attributes,both the 2'-F and 2'-OMe moieties leave much functional potential to be desired.…”
mentioning
confidence: 99%
“…It should be mentioned here that Romesberg and coll. ( 48 ) managed to develop an engineered DNA polymerase capable of amplifying directly RNA and modified RNA such as 2′ fluoro RNA. Also, these authors developed a third type of base pair that could be tried in the near future to be incorporated by CS13 mutant ( 49 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…To allow substrate tolerance of Thermococcus gorgonarius DNA polymerase, the group developed a mutant enzyme capable of synthesizing RNA and modified nucleic acids while retaining its stability toward heat denaturation [ 70 ]. The Romesberg group recently reported a variant of the Stoffel fragment of the Taq DNA polymerase (SFM4-3) [ 71 ] that was shown to exponentially amplify two different RNA fragments from one DNA template, primed by two asymmetric DNA oligonucleotides [ 5 ] (Fig. 2c ).…”
Section: Sample Preparationmentioning
confidence: 99%